2019
DOI: 10.1542/peds.2018-2108
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Risk Factors for Subsequent Physical Abuse Hospitalizations

Abstract: OBJECTIVES:To describe the prevalence of risk factors for abuse and newborns' risks for physical abuse hospitalizations during early infancy. METHODS:We created a nationally representative US birth cohort using the 2013 and 2014 Nationwide Readmissions Databases. Newborns were characterized by demographics, prematurity or low birth weight (LBW), intrauterine drug exposure, and medical complexity (including birth defects). Newborns were tracked for 6 months from their birth hospitalization, and subsequent abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Common maternal characteristics were socioeconomic status (N = 11) (Bauer et al, 2005; Lewis et al, 1997; Prindle et al, 2018; Puls et al, 2019; Putnam-Hornstein et al, 2016; Rebbe et al, 2019b; Shah et al, 2012; Smith & Testa, 2002; Williams-Petersen et al, 1994; Witt et al, 2017), race/ethnicity (N = 10) (Bauer et al, 2005; Lewis et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Rebbe et al, 2019a, 2019b; Smith & Testa, 2002; Sun et al, 2007; Wasserman & Leventhal, 1993; Witt et al, 2017), age (N = 9) (Bauer et al, 2005; Frame, 2002; Lewis et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Rebbe et al, 2019a; Shah et al, 2012; Sun et al, 2007; Williams-Petersen et al, 1994), timing of prenatal care (N = 7) (Doris et al, 2006; Friedman et al, 2009; Leventhal et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Rebbe et al, 2019a, 2019b), history of prior maltreatment (N = 7) (Doris et al, 2006; Frame, 2002; Friedman et al, 2009; Leventhal et al, 1997; Smith & Testa, 2002; Sun et al, 2007; Williams-Petersen et al, 1994), and partner status (N = 6) (Lewis et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Shah et al, 2012; Smith & Testa, 2002). Common infant characteristics were infant size (N = 5) (Bauer et al, 2005; P...…”
Section: Resultsmentioning
confidence: 99%
“…Common maternal characteristics were socioeconomic status (N = 11) (Bauer et al, 2005; Lewis et al, 1997; Prindle et al, 2018; Puls et al, 2019; Putnam-Hornstein et al, 2016; Rebbe et al, 2019b; Shah et al, 2012; Smith & Testa, 2002; Williams-Petersen et al, 1994; Witt et al, 2017), race/ethnicity (N = 10) (Bauer et al, 2005; Lewis et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Rebbe et al, 2019a, 2019b; Smith & Testa, 2002; Sun et al, 2007; Wasserman & Leventhal, 1993; Witt et al, 2017), age (N = 9) (Bauer et al, 2005; Frame, 2002; Lewis et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Rebbe et al, 2019a; Shah et al, 2012; Sun et al, 2007; Williams-Petersen et al, 1994), timing of prenatal care (N = 7) (Doris et al, 2006; Friedman et al, 2009; Leventhal et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Rebbe et al, 2019a, 2019b), history of prior maltreatment (N = 7) (Doris et al, 2006; Frame, 2002; Friedman et al, 2009; Leventhal et al, 1997; Smith & Testa, 2002; Sun et al, 2007; Williams-Petersen et al, 1994), and partner status (N = 6) (Lewis et al, 1997; Prindle et al, 2018; Putnam-Hornstein et al, 2016; Shah et al, 2012; Smith & Testa, 2002). Common infant characteristics were infant size (N = 5) (Bauer et al, 2005; P...…”
Section: Resultsmentioning
confidence: 99%
“…Women organising care themselves searched the Internet for personal details of midwives and contacted them themselves. Risk factors for a vulnerable transition into parenthood with associated risks for impaired child development and for child abuse such as teenage mother, single mother, no vocational education, jobless, poverty, migration, drug abuse, domestic violence, multiples, preterm birth or child with congenital malformation were investigated as single and cumulative factors [27,28]. Descriptive statistics were computed according to the type of variables and study groups were compared using chi squared tests for categorical variables and Mann-Whitney-U-test for metric variables.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Recent studies have examined clinical outcomes among substance exposed infants (Agrawal et al, 2019; Hwang et al, 2017; Puls et al, 2019; Uebel et al, 2015; Witt et al, 2017) with prior studies demonstrating an increased risk of hospitalization for a variety of conditions during infancy and early childhood among substance exposed infants compared to their unexposed counterparts (Hwang et al, 2017; Puls et al, 2019; Uebel et al, 2015; Witt et al, 2017). For example, a cohort study in Washington State found an increased risk of re-hospitalization prior to age five years for infants with neonatal abstinence syndrome (NAS; i.e.…”
mentioning
confidence: 99%
“…Among 2003–2009 births in Massachusetts, infants born to mothers with substance use disorders in pregnancy had higher use of hospital-based care, including hospital admissions, observational stays, and emergency department visits, in the first year of life compared to infants of mothers without a documented substance use disorder in pregnancy (Hwang et al, 2017). In a nationally-representative sample of 2013–2014 births, prenatal substance exposure was associated with an increased risk of physical abuse hospitalizations prior to age 6 months (Puls et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation